A REVIEW ON THE EFFECTIVENESS OF CURRENT APPROACHES TO STRESS MANAGEMENT - Dubey, Chetan Kumar; chaturvedi, Sarika; chaturvedi, Shilpi (Asian Journal of Pharmaceutical Research and Development, 2018)
Stress is your body’s way of responding to any kind of demand or threat. When you sense danger—whether it’s real or imagined—the body's defenses kick into high gear in a rapid, automatic process known as the “fight-or-flight” reaction or the "stress response. The stress response is the body’s way of protecting you. When working properly, it helps you stay focused, energetic and alert. In emergency situations, stress can save your life—giving you extra strength to defend yourself, for example, or spurring you to slam on the brakes to avoid an accident. Stress can also help you rise to meet challenges. It’s what keeps you on your toes during a presentation at work, sharpens your concentration when you’re attempting the game-winning free throw, or drives you to study for an exam when you'd rather be watching TV. But beyond a certain point, stress stops being helpful and starts causing major damage to your health, your mood, your productivity, your relationships, and your quality of life. Keywords- Stress, psychology of stress, HPA axis, ACTH